Terahertz ultrasensitive biosensing metamaterial and metasurface based on spoof surface plasmon polaritons. (28th November 2018) - Cheng, Dong; Zhang, Bao; Liu, Guo; Wang, Jianxun; Luo, Yong
Abstract: As a promising candidate for rapid and ultrasensitive sensing of biomolecules, terahertz time‐domain spectroscopy (THz‐TDS) can be considered with superior performance in label‐free, noncontact, noninvasive, and nondestructive detection. In particular, almost significant conformational information can be captured with THz‐TDS. Meanwhile, terahertz (THz) metamaterial or metasurface biosensing chips based on THz‐TDS were proposed to promote the detection sensitivity within strong local field‐matter enhancement. In this paper, the ultrasensitive THz biosensing metamaterial and metasurface for DNA/RNA detecting based on spoof surface plasmon polaritons (SSPPs) is probed. The simulated results show that the maximum frequency sensitivity of the proposed metamaterial and metasurface for DNA/RNA biosensing can respectively approach to 2.52 THz/refractive index unit (RIU) and 2.23 THz/RIU. In addition, the film thickness sensitivities of metamaterial and metasurface biosensors are respectively higher than 71.1 GHz/μm and 79.2 GHz/μm when the thickness of biomaterial is thinner than 4 μm. All these ascendant performances achieved in the proposed metamaterial and metasurface biosensors can be realized and exploited for ultrasensitive biomolecules detection, health monitoring, medical film sensing, and safety inspection in THz regime.